Determination of Equivalence Conductance and Dissociation Constant from Conductance Method - Parsania, P.H. (Asian Journal of Chemistry, 2010)
The solubility of saturated furyl acrylic acid (FAA) in water at 31ºC was determined by conductometric titration using 0.1N NaOH. The equivalence conductance of FAA at infinite dilution was determined from λ0 values of Na–FAA, HCl and NaCl at 31ºC. The degree of dissociation and dissociation constant at several dilutions were determined according to Ostwald dilution law. True dissociation constant is determined by applying Debye-Hückel limiting law. The values of λ0 and K are 394.81 and 3.963 x 10–5, respectively.